(untitled) (Филолошки студии, 2019)
The article deals with three different variants of reconstruction and interpretation Slavic mythology in three poetic cycles of the beginning 20th century. Three poets create specific poetic pictures of Slavic past. All of them – Konstantin Balmont’s idyllic world of past, Sergey Gorodetsky’s cruel world of primitive passions and Aleksey Kondratyev’s universal picture of world cultural relationships – try to understand beginnings of national character.